PENERAPAN MEDIA TEKA-TEKI SILANG UNTUK MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA KELAS IV A SDN MANUKAN KULON II/499 SURABAYA - Moh. Ramdani; Mintohari Mintohari; Wandik Wandik (ENTINAS: Jurnal Pendidikan dan Teknologi Pembelajaran, 2023)
This study aims to determine improve the learning outcomes of the fourth grades of SD Negeri Manukan Kulon II/499, in Indonesian studies using the Crossword Puzzle. This research was used the Classroom Action Research (CAR). It was conducted in three cycles. Each cycle includes four phases, namely planning, action, observation, and reflection. The subjects were students of class IV A, totaling 26 students, consisting of 13 male and 13 female students. The research was conducted in the second semester of the academic year 2022/2023. The minimum completeness criteria (KKM) for Indonesian studies in SD Negeri Manukan Kulon II/499 is 75. Based on the research results, student learning outcomes have increased in the realm of knowledge, attitudes and skills. The results of students in the first cycle achieve mastery of 64% with an average of learning outcomes of 76, the second cycle achieve mastery of 77% with an average of learning outcomes of 84. And the three cycle achieve mastery of 92% with an average of learning outcomes of 90. In the realm of attitudes, student learning outcomes increased from cycles I, II and III by reaching the excellent category. In the realm of skills, student learning outcomes also experienced an increase from cycles I, II and III by reaching the very good category. From the results of this study, it can be interpreted that learning media for crossword puzzles can improve learning outcomes in Indonesian subjects.